Pemodelan Pemulihan Sistem 500 Kv Saat Terjadi Blackout Dengan Simulasi Digsilent - Samsurizal Samsurizal; Andi Makkulau (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2021)
The electric power system network must be maintained in its operation. The stability of the frequency in the balance between the power supply and the load is the main thing. In the event of a major disturbance, where many generating units are out of operation so that the system's generation capability is much lower than the load requirement, it can cause blackouts in the system. If this happens, the power system must immediately restore its generating capacity so that it can immediately serve the load or electricity users. In the simulation using DIgSILENT, it was found that the amount of load that must be sent by the Saguling PLTA to the Suralaya PLTU for the start-up process is 52.22 MW. And after the Suralaya PLTU is ready to operate, a recovery process is carried out on the 500 kV network by restoring GITET on the western system by paying attention to the frequency so that it returns to normal frequency. By using the software DIgSILENT 15.1.7. From the simulation results, the results showed that the Suralaya GITET recovered at a frequency of 50.072 Hz, 49.825 Hz at the Cilegon Baru GITET, 49.825 Hz at the Cibinong GITET, 49.953 Hz at the Bekasi GITET, and 50.064 Hz GITET in Cawang. While GITET Gandul at 49.866 Hz and GITET Kembangan at 50.078.